War, Culture and Lebensreform. Germany’s way to itself? A few considerations on Simmel’s war writings - Portioli, Claudia (Simmel Studies)

(untitled) (Georg Simmel Gesellschaft, 2018)
The paper explores Simmel’s writings explicitly dedicated to the war and uses them as sources for investigating the underlying social and cultural context with which Simmel interacted. In particular, it takes into account possible links between Simmel’s considerations on the relationship between war and the crises of modern culture and the multifaceted life-reform movements developed in pre-war Germany. The latter movements, which arose in the last decades of the 19th century, expressed a critical reaction to the negative characteristics of modern German society and a search for alternative lifestyles. The paper also investigates the sense of a few inconsistencies found when comparing specific passages that Simmel wrote on the same topics during the war. In the second part, the author considers how the development of Simmel’s narrative on the war affects several key elements of his thought such as qualitative individualism, subjective culture, identity and/or the issue of a new order of values. The author suggests that all these elements become part of an intertwined tissue of arguments which delineate Simmel’s attempt, as an individual, to react to a widespread cultural and spiritual distress.